Identifikasi Tumbuhan Mangrove di Kawasan Pesisir Pantai Desa Pakowa Bunta Kecamatan Nuhon Kabupaten Banggai - Mitha F Karim; Moh. Fahri Haruna; Alwia Samaduri (Jurnal Biologi Babasal, 2023)
Abstract : Many people do not know that mangrove plants have scientific names and are divided into several types.This type of research uses descriptive qualitative research. The  research was conducted on the coast of Pakowa Bunta Village, Nuhon District, Banggai Regency in Bulan July – August 2020. The population in this study were all mangrove plants obtained when  conducting research using roaming techniques and is considered to be representative of the population based on their species to be indentified. The method or technique in  collecting data used is the roaming technique, which means that the researcher explores the research location. The results of the research data in the form of samples obtained on the coast of Pakowa Bunta Village in the  form of mangrove plant species and field notes in the from of mangrove morphological forms, pictures, identification will be carried out based on the literarure  that book used and described. Based on the results of data collection obtained by using the roaming method throughout the reseacrch location, identifying samples with litelature or references in the form of a book of determination. Researchers  obtained 7 types of mangroves in the research location, namely : Senorita alba, Rhizophora apiculata, Avicennia alba, Bruguiera sexangula, Ceriops decandra, and Nypa fruticans. The 6 types  of mangrove plants can be classified into 4 families, namely Sonneratiaceae, Avicenniaceae, Arecaceae and Rhizophoraceae. The six types of mangroves except  for Nypa fruticans are the main components (True Mangrove) while Nypa fruticans are additional components (Mangrove Associations and acer). Keywords: Identification, Mangrove Plants, Pakowa Bunta.